Structure and catalytic mechanism of human protein tyrosine phosphatome - Kim, Seung Jun (Korean Society for Biochemistry and Molecular Biology, 2012)
Together with protein tyrosine kinases (PTKs), protein tyrosine phosphatases (PTPs) serve as hallmarks in cellular signal transduction by controlling the reversible phosphorylation of their substrates. The human genome is estimated to encode more than 100 PTPs, which can be divided into eleven sub-groups according to their structural and functional characteristics. All the crystal structures of catalytic domains of sub-groups have been elucidated, enabling us to understand their precise catalytic mechanism and to compare their structures across all sub-groups. In this review, I describe the structure and mechanism of catalytic domains of PTPs in the structural context. [BMB Reports 2012; 45(12): 693-699]